Knowledge, attitude, and behaviour of patients towards use of cough and cold preparations: a comprehensive surveyKnowledge, attitude, and behaviour of patients towards use of cough and cold preparations: a comprehensive survey - Ambikar, Digambar B.; Mittal, Vishesh S. (International Journal Of Community Medicine And Public Health, 2022)
Background: Cough, cold and related discomforts are the most common discomforts affecting general population, which can adversely affects subjects’ quality of life due to its physical, social, and psychological effects. To know the patients perception towards cough and cold preparation is need of hour for health care industry. Methods: This study investigated the knowledge, attitude and behaviour of patients toward use of cough and cold preparations. Questionnaires were distributed to patients approaching to pharmacy for purchasing these drugs. Results: The age group was from 17 to 55. In our study 66 % of patients reported that they prefer liquid oral formulation over other dosage form. Further in syrup formulations. Around 59% of patients are prescribed with some of the cough syrup while remaining 41% are purchasing OTC preparations. But 58% patients still not aware with concept of OTC medicine. Further 51% patients are not aware about the adverse effects of such preparations. Conclusions: The study provides important insights into the use of cough and cold medications in general populations especially about OTC medications. There is need to create awareness in patients about safe use of these preparation, as the safety profile of drugs included in cough syrup is very important here.